Eba! Educação com base em arte: cenas de uma experiência de aprender a ensinar com a linguagem da arte - Arantes, Thays Gonçalves (2009)
The aim of this dissertation is to critically describe and analyze: (1) an experience of learning to teach with the language of art; (2) the teacher education, specially the teachers educator, in the experience of learning to teach with the language of art; This research was developed in the stage of Narrative Inquiry (CONNELLY; CLANDININ, 1988, 1990, 1995, 1998, 2004, CLANDININ; CONNELLY, 1986, 1994, 1995, 2000, CLANDININ, 2007, MELLO, 1999, 2004) that presents life and educational experiences as a way to teachers reflection and in the stage of Art-based Research (EISNER,1991, 2002, DIAMOND, 1997,1999, TELLES, 1991, 1997, 1998a, 1998 b, 1999, 2004, 2005, 2007, DUARTE, 2001). The generation of field texts was motivated or resulted, in the most, by artistic activities and the research text was composed by means of many forms of expression of the language of art. In order to develop this research, part of the composition of the field texts took place during an Art-Based Education course, at a Brazilian university, with 28 teachers from many knowledge areas. The field texts were composed by the inscription forms, the teacher s educator course plans, audio records, reflective diaries, narrative analyses and analyses of the artistic and non-artistic productions of the course participants. The transformation of the field texts into research text took place with the creation of themes and the meaning composition based on the studies of Ely, Vinz, Downing e Anzul (2001). From the meaning composition of the field texts we were able to see art-based education as a space that makes possible the teacher education, working with diversity and valuing cognition and emotions. The meaning composition also showed us the language of art as an instrument that allows teachers to narrate, reflect and share their experiences of life and education using different forms of expression of the language of art.